RARE EARTH AND YTTRIUM PHOSPHATE SOLUBILITIES IN AQUEOUS SOLUTION - Liu X.; Byrne R.H. (My University, 1997)
Rare earth and yttrium phosphate solubility products range over more than 1 order of magnitude. Minimum solubilities are observed for light rare earths between Ce and Sm. For the elements Ce, Pr, Nd, and Sm solubility products (log K0sp (M) = log ([M3+i][PO3-4])) at zero ionic strength and 25°C can be approximated as log K0sp(M) = -26.3 +/- 0.2. Rare earth phosphate solubility products for well-aged, coarse precipitates increase substantially between Sm and Lu, with log K0sp(Lu) estimated as -24.7. The solubility product of Y is similar to that of Ho (log K0sp(Y) = -25.0) and is much higher than those of all light rare earths. The solubility product of La is substantially larger than that of Ce (log K0sp(La) - log K0sp(Ce) ~ 0.5). Solubility products are strongly dependent on the conditions of solid phase formation. Fresh precipitates are much more soluble than slowly formed, well-aged, coarse precipitates. The pattern of rare earth and yttrium phosphate solubility products is generally similar to the fractionation patterns which are developed during phosphate coprecipitation.